Indonesia Military Research and Development in Dealing with the Sixth Generation Warfare: The Use of Artificial Intelligence in War Operations - Irvan Arianto Randa Lembang; Romie Oktavianus Bura; R Djoko Andreas Navalino; Lutfi Adin Affandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Technological advancement has forced the international community to deal with the sixth generation of war, which is a conflict involving the most advanced robotics, artificial intelligence (AI), and satellite technology. This shows that warfare has evolved beyond traditional tactics because parties are no longer required to engage in face-to-face combat as they did during the first generation of conflicts. Although the